Eosinophilic drug reactions detected by a prospective pharmacovigilance programme in a tertiary hospital. (12th October 2016) - Ramírez, Elena; Medrano‐Casique, Nicolás; Tong, Hoi Y.; Bellón, Teresa; Cabañas, Rosario; Fiandor, Ana; González‐Ramos, Jessica; Herranz, Pedro; Trigo, Elena; Muñoz, Mario; Borobia, Alberto M.; Carcas, Antonio J.; et al.
Abstract : Aim: We conducted a prospective evaluation of all eosinophilic drug reactions (EDRs) through the Prospective Pharmacovigilance Program from Laboratory Signals at Hospital to find out the incidence and distribution of these entities in our hospital, their causative drugs, and predictors. Methods: All peripheral eosinophilia >700 × 10 6  cells l −1 detected at admission or during hospitalisation, were prospectively monitored over 42 months. The spectrum of the localised or systemic manifestation of EDR, the incidence, the distribution of causative drugs, and the predictors were analysed. Results: The incidence of EDR was 16.67 (95% Poisson confidence interval [CI]: 9.90–25.98) per 10 000 admissions. Of 274 cases of EDR, 154 (56.2%) cases in 148 patients were asymptomatic hypereosinophilia. In the remaining 120 (43.8%) cases, there was other involvement. Skin and soft tissue reactions were detected in 36 (13.1%) cases; visceral EDRs in 19(7.0%) cases; and drug‐induced eosinophilic cutaneous and visceral manifestations were detected in the remaining 65 (23.7%) cases, 64 of which were potential drug reaction with eosinophilia and systemic symptoms (DRESS). After adjusting for age, sex, and hospitalisation wards, predictors of symptomatic eosinophilia were earlier onset of eosinophilia (hazard ratio [HR], 10.49; 95%CI: 3.13–35.16) higher eosinophil count (HR, 8.51; 95%CI: 3.28–22.08), and a delayed onset of corticosteroids (HR, 1.34; 95%CI: 1.01–1.73). A higher eosinophil count in patients with DRESS was significantly associated with greater impairment of liver function, prolonged hospitalisation, higher cumulative doses of corticosteroids, and if hypogammaglobinaemia was detected, a reactivation of human‐herpesvirus 6 was subsequently detected. Conclusions: Half (53.3%, 64/120 cases) of symptomatic EDRs were potential DRESS. The main predictor of severity of EDR was an early severe eosinophilia.